Effect of exercise type on men’s physical fitness and body composition: a systematic review and meta-analysis - Ki-Woong Noh; Eui-Kyoung Seo; Sok Park (Journal of Men's Health, 2025)
Background: Resistance training (RT), endurance training (ET) and concurrent training (CT) have been extensively researched for their diverse effects, including increases in muscle strength and mass, reductions in body fat, and improvements in cardiorespiratory fitness. This systematic review with meta-analysis aimed to summarize and analyse the effect of exercise type on men’s physical fitness and body composition. Methods: Extensive searches were conducted in the English biomedical databases PubMed, MEDLINE, Web of Science and CINAHL, as well as the EBSCO database. Cochrane’s risk of bias was used to assess the quality and risk of bias of the selected articles. STATA/MP 18 version was used for the meta-analysis. Results: A total of 5137 articles were retrieved from five database. 17 randomized controlled trials were selected for the analysis. The CT group exhibited the highest effect size (ES) across all variables. In the leg press, CT (d = 1.65) displayed the largest effect size, with RT (d = 1.65) demonstrating similar trends as CT. In the bench press, CT (d = 2.25) demonstrated the largest effect size, whereas RT (d = 2.21) exhibited a level comparable to that of CT. For maximal oxygen consumption max (VO2max), CT (d = 0.94) displayed the largest ES and ET (d = 0.90) showed an ES similar to that of CT. CT (d = 0.22) and RT (d = 0.20) exhibited low effect sizes in the lean body mass. The CT intervention group (d = −0.43) demonstrated the largest reduction in fat mass. Conclusions: CT demonstrated superior effectiveness in preventing muscle loss, obesity and enhancing physical fitness in men. This underscores its potential for practical exercise planning and future research on exercise types. However, further investigation is warranted due to limitations such as the heterogeneity of analyzed studies, differences in exercise intervention methods and variations in subjects’ ages. The PROSPERO Registration: CRD42024549681, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024549681.